Legal Protection for Creditors over State Confiscation of Fiduciary Guarantee Objects - Trisadini Prasastinah Usanti; A Shomad; Ari Kurniawan; Bimo Ario Tejo (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2026)
Fiduciary guarantee is a recognized security institution in Indonesian law in which the collateral object remains in the possession of the fiduciary grantor. Although registration confers a right in rem on the fiduciary recipient, this continued possession exposes the object to confiscation by the state where the debtor uses it to commit a crime such as illegal logging. This study examines the legal protection available to a creditor as fiduciary recipient once the collateral object has been confiscated by the state under a court decision, using normative legal research with statute, conceptual, and case approaches centered on Decision Number 18/Pdt.G/2015/PN Ktp. The findings show that two attributes of the right in rem attached to fiduciary guarantee, the absolute right and the droit de suite principle, cannot be enforced once the object has been confiscated, since it passes into state ownership and may no longer be used by any party. Confiscation does not extinguish the principal debt, so the debtor remains obligated to settle it, but the creditor's standing is reduced from preferred to concurrent creditor. The creditor's remaining remedies are to demand a substitute guarantee from the debtor or, failing that, to file a civil claim grounded in unlawful conduct under Article 1365 of the Civil Code.